To Study the Factors Affecting of GEN Z Visit to Various Heritage Site - Avadhi Kothiya; Krishna Trivedi; Jignesh Vidani (MultiTech Publisher, 2024)
Running into research, it investigates the various features that put Generation Z in travel destinations pertaining to cultural tourism, with a particular aim to understand the trends framing incidences of cultural interactions in the present media age. While heritage tourism thus encounters a Generation Z more digital-savvy, digitally-adapted, and access-focused in finding real culture experiences, the research pinpoints the setbacks prompting Generation Z to visit cultural heritage sites among new entrenchment improvement technologies such as augmented reality and virtual reality; the effect of their peers and social media influence; and other factors such as sustainability, diversity, and the requisite of engaging activity-based learning. The research therefore underscores the sustainability and corporate greening view since Gen Z is said to care about the environment. The study thus offers not only valuable theoretical inputs to the literature on consumer behaviour but also actionable implications for the management of heritage sites and tourism organisations in terms of guidelines for communicating with and marketing to Gen Z generation; this includes embracing the role of digital technologies in experiential interactions, lower price points, and so on. These calls from theory to research, therefore, create an urgency in rethinking the existing notion of heritage consumption regarding multicultural tourist digital interactions and their implications for sustainability and cultural authenticity. This research thus contributes to the ongoing discourse on engaging with heritage tourism for Generation Z and strategizes on the possible preservation of this object of interest against forever changing into the cultural and media environment